A Shorterm Study- Aquanalco- Assessing Industrial Impact on Aquatic Ecosystem in Damanjodi Area, Korput District, Southern Odisha, India - Das, Udaya Kumar; Jena , Bandana; Guntha , Gayatri; Majhi, Jashmi Prabha; Priyadarsini , Madhusmita; Shailaja, Sejal; Benia , S Spandita; Mallick , Subhashree; Sagar , Swandita Saijal; Mohapatra , Sunil Kumar (American Journal of Biology and Natural Sciences, 2025)
A three months study was undertaken in the Nalco Damanjodi Area of Koraput district. This fulfils the minor and short term MSc dissertation study on aquatic ecosystems. The landscape is high altitude mountain area with valleys and rifts. Some area have paddy fields which were latter converted to Ash ponds literally the reservoirs of the swage effluents from the Almina Refineries plants at Damanajodi. One another storage pond is Red mud pond which is more toxic, non-living area of the industries, other aquatic waterbodies are Nalco recreation Fish pond, Kolab Dam, Panchupatimali streams. It is seen that the Red Mud pond have Dissolved Oxygen (DO) less than 1mg/L, the PH is 13-14 which is highly alkaline even corrosive to naked hands. and does not sustain no life even bacteria and algae. The Ash pond water has PH is 11- 12 hich is also highly alkaline but not corrosive. The DO is 1-2mg/L and no titration is obtained. This aquatic waterbody has little life supporting phases, here frogs and aquatic birds can sim and float, they have no aquatic respiration and can just occupy a space to live some spare of time without feeding activity as no other small aquatic fauna has fishes existed. Little aquatic grasses and wild paddy is present in the submerged parts of Ash pond. The Nalco recreational pond in NALCO township has life sustain capability having varied fishes, toads and birds like cormorants, egrets, lesser whistling ducks, frogs, fishes, tree geckos freshwater terrapins, crustacean, prawns, crabs and waterbugs, earhworms, leaches etc. The Pancpatimal hill stream has life supporting properties with High DO 12.39 hich is higher vales according to the life suitable for hill stream fishes, and other aquatic life forms here as the piped stream ater that used for drinking at mining site has DO of 13.41 Mg/ L being the highest in the study. The Kolab water has DO of 12.39 Mg/ L which is suitable for aquatic life in dam after. No such studies were done in the this themes in a restricted area like Nalco mining area which is a high security Zone of the country.